PROPOSTA METODOLÓGICA PARA ELABORAÇÃO ORÇAMENTÁRIA DE TESTES DE SOFTWARE - Matieli, Luciana Vago (2014)
The methodologies employed in the market relative of pricing practices related to the activity of software testing are strongly based on empiricism without parameters or widely accepted criteria, which does not give proper credibility in terms of time and cost for both contractors, as to third parties. This study aims to propose a methodology to estimate software testing, contributing to improvement of that process. In terms of methodology, the study relies on scientific and technical literature on the subject, interviews and consultations with technical experts (experts) of a third party, providing service to a large Brazilian company in the telecommunications industry in order to raise theoretically and empirically the main parameters to be considered, as well as their relative weights. As conclusions, there is the possibility of designing the proposed method, representing significant contribution to increasing the transparency of the testing and the establishment of more reliable parameters in terms of time and cost of software testing services projects.